(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
The development of cities in Central Asia and the study of the ways of their development is one of the factors determining the prospects of urban development in Uzbekistan at present. It is known that the study of any event or reality necessarily requires analyzing its evolutionary process. Tashkent, among all historical cities of the world, has always had a special appeal due to its central position at the crossroads of East and West. Tashkent is a special city with an interesting history of urban development.